Classification market vacancies in information technology by profession Software Engineer - Kruglik, V. (Problems of Engineer-Pedagogical Education, 2018)
The article is devoted with various data market research work conducted in Ukraine in recent years which says that in several years the championship in rating of the most promising professions will be IT-specialists. According to statistics positions which can run future software engineer after graduation is determined. Database of vacancies in different countries are analyzed. With the analysis of foreign countries and Ukrainian the classification of positions in the field of information technology in the profession software engineer is arranged. The study analyzed the classification of professions for determination of professional work names in the programming sphere activity. It is determined that the labor market there is a high order for qualified programming professional specialists. It is noted that the requirements for candidates to positions is differ considerable variety because it is connected with a wide range of technologies and programming languages and areas of future software engineers.